Overlap of dietary niche and electivity of three shrimp species (Crustacea, Decapoda) in a tropical coastal lagoon (Rio de Janeiro, Brazil) - Albertoni,Edélti Faria (2003)
Three species of shrimp, Farfantepenaeus brasiliensis (Latreille, 1817), F. paulensis (Pérez-Farfante, 1967) (Penaeidae) and Macrobrachium acanthurus (Wiegmann, 1836) (Palaemonidae) were sampled at the Imboassica lagoon (Rio de Janeiro State, Brazil), in order to estimate the overlap of dietary niches and electivity of their prey, through the analysis of the fauna associated with the macroalgae Chara and of the benthic fauna on the sediment. The overlap of dietary niches was estimated using five indexes. A total of 495 F. brasiliensis, 131 F. paulensis and 102 M. acanthurus stomachs were examined. The results of the different indexes of niche overlap exhibited the same general trend in the three species, indicating a high degree of homogeneity in the diet of the two species of Penaeidae (between 75 and 100%) and a smaller overlap between each Penaeidae species and M. acanthurus (between 23 and 68%). The species presented selective predation, with differences in the two studied habitats. The results show that the three species are omnivorous, with a varied diet including components of benthic macrofauna and those associated with the macroalgae Chara, plant fragments and detritus, and that there are good conditions in the Imboassica lagoon for the development of these species.